PENGARUH TREND FASHION MUSLIM DAN MEDIA SOSIAL TERHADAP PERILAKU KOSUMTIF MAHASISWI UNIVERSITAS MERDEKA PASURUAN - Adinda Rizqy Kusuma Dewi; Pudyaningsih, Ratna; Mufidah, Eva (Jurnal Pijar, 2023)
The objectives of this research are: 1) To determine the influence of Muslim Fashion Trends and Social Media simultaneously on female students' consumer behavior. 2) To determine the partial influence of Muslim Fashion Trends on the Consumer Behavior of Female Students. 3) To determine the influence of Social Media on Female Students' Consumptive Behavior. This research uses Quantitative Research methods. The population in this study were all female students at Merdeka Pasuruan University who wore the hijab. The number of samples in this study was 53 respondents. The data collection technique uses the observation method through distributing questionnaires and processing using SPSS. The analysis technique used uses descriptive statistical analysis. The research results show that: 1) Muslim Fashion Trends and Social Media simultaneously have a significant influence on female students' consumer behavior by 47% and the remaining 53% is influenced by other variables. 2) Muslim Fashion Trends partially have a significant influence on Female Students' Consumptive Behavior. 3) Social Media partially has a significant effect on the consumer behavior of female students.